The Effect of Group Guidance Services with Modeling Techniques to Improve Discipline for Class VIII Students at SMP Islam Al-Khoiriyah Petarukan Pemalang: Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Modelling Untuk Meningkatkan Disiplin Siswa Kelas VIII di SMP Islam Al-Khoiriyah Petarukan Pemalang - Kamal, Lutfi Athoillah (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Abstract: The background in this study is the low discipline attitude of students in class VIII Islamic Junior High School Al-Khoiriyah Petarukan Pemalang. This study aims to determine whether there is an effect of group guidance with modeling techniques to improve the discipline attitude of class VIII students of SMP Islam Al Khoiriyah Petarukan Pemalang. The hypothesis in this study is that there is an effect of group guidance with modeling techniques on the discipline of class VIII students of SMP Islam Al Khoiriyah Petarukan Pemalang The population of this study were all students of class VIII SMP Islam Al Khoiriyah Petarukan Pemalang with a total of 142 students. The research sample was taken by using cluster random sampling technique so that the number of samples in this study was 30 students. There are two variables used, namely group guidance with modeling techniques as the independent variable, which is symbolized by (X) and student discipline as the dependent variable which is symbolized by (Y). The data collection method used a scale in the form of a student discipline scale using four alternative choices, namely strongly agree (SS), agree (S), disagree (TS), and strongly disagree (STS). The research method used in finding and determining validity is using the product moment formula. Based on the results of the validity test of the student discipline psychological scale, from 32 statements there are 20 valid items. This research was carried out at the Al-Khoiriyah Islamic Junior High School Petarukan Pemalang, the 2020/2021 academic year. The research instrument of the two variables has been tested for validity and reliability. Based on the results of the analysis that has been carried out from the data from the psychological scale assessment of student discipline, it shows tcount 21.12 > ttable 2.145. Thus this study concludes that the hypothesis which states "There is an Influence of Group Guidance Services with Modeling Techniques on Discipline in VIII grade students of SMP Islam Al - Khoiriyah Petarukan Pemalang". Key Words: Group Guidance, Modeling Techniques, Student Discipline